An insight into the mechanism of surface conductivity in thin film diamond - Looi, H; Pang, L; Molloy, AB; Jones, F; Foord, J; Jackman, R (1998)
Diamond containing hydrogen at or near the surface displays p-type conductivity. The origin of this effect has been controversial. We have used I-V, Hall effect, SIMS, Raman, UPS and XPS to study hydrogenated polycrystalline CVD diamond films. The direct formation of acceptor states by hydrogen, which resides within the top 20 nm of the film, is the origin of the carriers present rather than surface band bending. Up to 1019 holes cm-3 can be measured and mobilities as high as 70 cm2 Vs-1 recorded. H-termination of the surface is important for the formation of high quality metal-diamond interfaces. © 1998 Elsevier Science S.A.